Budesonide/salmeterol in fixed-dose combination for the treatment of asthma. (1st February 2016) - Popov, Todor A.; De Niet, Sophie; Vanderbist, Francis
Abstract: Fixed dose combinations (FDC) of inhaled corticosteroid (ICS) and long-acting beta agonist (LABA) are well established in asthma treatment. The budesonide/salmeterol (B/S) FDC is now about to reach the market. It is provided as powder in hard capsules of two strengths: 120/20μg and 240/20μg when expressed as delivered doses, equivalent to 150/25μg and 300/25μg when expressed as nominal doses. Its development involved 9 pharmacokinetic (320 subjects), 3 phase II (123 subjects) and 4 phase III (1206 patients with different asthma severity) studies. Delivery is effectuated via low resistance inhaler device, Axahaler®, generating also fine particles targeting the small airways. B/S safety, assessed in 1401 subjects, did not outline novel concerns specific for this FDC. In conclusion, the B/S dry powder FDC can be used for asthma treatment in adults not adequately controlled on ICS alone, or to maintain control of ICS/LABA treated patients, in whom switching to alternative FDC is indicated.